Setting Differential Relay Transformer (87T) dengan Pertimbangan Vector Group pada PLTU Tenayan 2x110 MW - Pujiantara, Margo; Rizki Firdausi, Teuku; Raki Mahindara, Vincentius; Lystianingrum, Vita (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2021)
PT. Pembangkitan Jawa Bali (PJB) Unit Bisnis Jasa Operasi dan Pemeliharaan (UBJOM) PLTU Tenayan has protection equipment that serves as a support for power generation activities. One of the main protections used on PLTU Tenayan is differential relay transformer (87T). This Differential relay serves to protect main transformers from interference and work quickly and selectively in breaking interruptions. In electrical systems PLTU Tenayan, the main transformer and transformer UAT have a vector group configuration, thus causing the current flowing on both sides of the transformer will be different, and the current perceived by CT on both sides of the transformer will be different, so that the relay operates without any interference. On 9 December 2018, there was a trip on the generator Unit 1 PLTU Tenayan, causing blackout. This incident was allegedly due to lightning strikes on the transmission side of 150 kV. In this research will be conducted analysis of differential relay transformer (87T) with the consideration of vector group on PLTU Tenayan 2x110 MW. Research method with simulation using ETAP software 12.6.0. The results of the analysis of the simulations and calculations in the value of Idiff 1.5 Ie and slope of 120%, this value will be used for the setting differential relay transformer. From the test results obtained that differential relay transformer only works when internal disruption only and does not operate when external interference. So differential relay transformer (87T) safe from fault trip and operation fault.